BIOREMEDIATION OF CONTAMINATED WASTE BY CADMIUM (Cd) IN WATERS USING INDIGEN BACTERIUM WITH EX-SITU WAY - Titik Wijayanti; Dinna Eka G. Lestari (JURNAL PENA SAINS, 2017)
The bioremediation technique for a contaminated liquid waste of heavy metals using indigenous bacteria is a convenient alternative to steps continues to be developed. The research aims to find out the effectiveness of an indigenous bacterial consortium in bioremediation of contaminated liquid waste by cadmium by ex-situ. Experiments were arranged in RAL made in ex-situ where a liquid waste industry was given five treatments, namely control and four indigenous bacterial consortia (A, D, E, and J) obtained from the isolation of bacteria originating from cadmium-contaminated of waste in Pasuruan district. Furthermore conducted observations of BOD5, COD, d.o. and Cd for seven days to find out the effectiveness of bioremediation. The results showed the four indigenous bacteria consortia have the bioremediation ability to reduce levels of cadmium, BOD5, COD, and increasing levels of DO. Indigenous bacterial consortia D has the best ability of liquid industrial waste bioremediation by ex-situ. Indigenous bacterial consortia J has the best of capacity reduction levels of cadmium, then the other of indigenous bacterial consortia.Keywords: indigenous bacterial, bioremediation, ex-situ, cadmium, liquid waste.